Complexometric Determination of Iron in Pharmaceutical Sample Using Hydroxytriazenes - Sharma, J.C.; Upadhyay, Mishika; Jain, C.P.; Dashora, Rekha (Asian Journal of Chemistry, 2010)
The present paper describes complexometric determination of Fe (III) using three hydroxytriazenes as metallochromic indicators in three medicines “Dexorange” (Franco Indian Pharmaceuticals Ltd.) “Austrin” (Weyeth Lederlab Ltd.) and “Fesovit” (Smith-Kline Beechen Pharmaceuticals). The hydroxytriazenes used were 3-hydroxy-3-methyl-1-psulphonamidophenyltriazene (HMSPT), 3-hydroxy-3-phenyl-1-p-chlorophenyltriazene (HPpCPT) and 3-hydroxy-3-phenyl-1-m-chlorophenyltriazene (HPmCPT), respectively.